Comparative Analysis of the Gut Microbiota of Mongolian Gazelle (Procapra gutturosa) Under Fragmented Habitats - Shi, Lupeng; Yang, Xiufeng; Dou, Huashan; Lyu, Tianshu; Wang, Lidong; Zhou, Shengyang; Shang, Yongquan; Dong, Yuehuan; Zhang, Honghai (Frontiers in Microbiology, 2022)
The existence of man-made facilities such as pasture fences makes the grassland ecosystem fragmented and endangers the survival of local wild animals. The Mongolian gazelle is highly sensitive to hunting and habitat destruction, and is one of the most threatened artiodactyls in Eurasia. It provides a critical model to studying gut microbiota under fragmented habitats. Therefore, we applied metagenomics sequencing to analyze the gut microbiota communities and functions of Mongolian gazelle under fragmented habitats. The results demonstrated that there were no significant differences in gut microbial communities between the different groups at the both phylum and genus level. The functional analyses showed that the Mongolian gazelle in fragmented habitat had a stronger ability to degrade naphthalene, but their ability to absorb carbohydrates was weaker. This study provided fundamental information about the gut microbiota of Mongolian gazelle, and we recommend reducing habitat fragmentation to better protect the Mongolian gazelle.